1996
DOI: 10.1021/jp961384b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Structure and Dynamics of the Hydration Shell of Alkaline and Alkaline-Earth Metal Cations

Abstract: Molecular dynamics simulations of hydrated alkaline and alkaline-earth metal cations at room temperature (T ) 300 K) were carried out using the CHARMM22 force field. Dynamic and static properties of systems containing one ion and 123 or 525 water molecules were investigated by analysis of trajectories of 1 ns duration and compared to experimental and theoretical results. In addition, the size and the direction of the elementary motions of both the ions and the water molecules were investigated on the scale of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
188
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(225 citation statements)
references
References 47 publications
34
188
3
Order By: Relevance
“…[31][32][33][34] In this context, an important conclusion of the present study is that E-fields can only enhance the H-bond structure of water, not disrupt it at any of the practically attainable field strengths. Past suggestions of the weakening of H-bond structure near the so-called "structure breaking" ions 5,6 or near charged electrodes 10,11 cannot be hence attributed to effect of E-field alone. The third category of results relates to the somewhat surprising finding that, within a certain window of field strength, H-bonds can stabilize molecules with their dipoles lying perpendicular to that of field.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[31][32][33][34] In this context, an important conclusion of the present study is that E-fields can only enhance the H-bond structure of water, not disrupt it at any of the practically attainable field strengths. Past suggestions of the weakening of H-bond structure near the so-called "structure breaking" ions 5,6 or near charged electrodes 10,11 cannot be hence attributed to effect of E-field alone. The third category of results relates to the somewhat surprising finding that, within a certain window of field strength, H-bonds can stabilize molecules with their dipoles lying perpendicular to that of field.…”
Section: Discussionmentioning
confidence: 90%
“…3 Despite substantial progress made in the past, what exactly is the internal structure of water in these situations, as well as what governs it, are still widely debated research topics. For example, while some studies [4][5][6] have supported the view of structure making and structure breaking by ionic solutes, others [7][8][9] have not. Similarly, in the case of water near charged surfaces, while experiments 10,11 reveal disruption of the H-bond network, simulations 12,13 show that the H-bond network is largely intact.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Grossfield concludes, based on calculated oxygenoxygen radial distribution functions of water molecules in the first solvation shell of ions compared to bulk water using a polarizable force field, that the presence of cations, but not anions, disrupts the water-water structure around the ions and that the extent of disruption is larger for Na + than for K + . 24 Obst and Bradaczek find a maximum in the number of acceptor hydrogen bonds formed by water molecules in the second solvation shell of Na + , 34 and Tongraar et al find, using mixed quantum mechanics/molecular mechanics methods, that Na + can orient water molecules beyond the first solvation shell whereas K + cannot. 35 Yet, as discussed above, the observed XA spectra of NaCl (aq) and KCl (aq) solutions exhibit negligible differences, which indicates that Na + and K + do not have very different effects on the nature of hydrogen bonds formed around these ions, which is inconsistent with many simulation results.…”
Section: Discussionmentioning
confidence: 99%
“…This broadly agrees with the coordination of the Mg 2+ ion by about 6 water molecules. 22,23 No DR signal arises from the [Mg(H 2 O) 6 ] 2+ complex because the symmetric coordination causes a vanishing net dipole moment. On the other hand, DR studies have shown that the dynamics of water molecules in the coordination shells of most inorganic anions is virtually indistinguishable from bulk water dynamics.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…31 Water molecules make and break hydrogen bonds with chloride ions on about the same timescale of ~3 ps as with each other, 10 whereas they remain in the first hydration shell of Mg 2+ for hundreds of picoseconds. 22,23 At a concentration of 4.4 M MgCl 2 , there are overall ~11 water molecules per cation, 8 ~7 of which form a stable hydration shell around the cation (Fig. 3(b) inset) in which rotation is strongly impeded.…”
mentioning
confidence: 99%